(untitled) (Universal International Scientific Journal, 2026)
This thesis examines pedagogical mechanisms for adapting the inclusive education process to the individual needs of students. The main goal of the study is to prepare future teachers for effective pedagogical activity in inclusive education and to identify effective methods for adapting the educational process to the individual needs of students. According to the results of the study, the need for systematic use of diagnostic, methodological, organizational and reflexive mechanisms is justified for the effective organization of inclusive education.